2019
DOI: 10.1097/icl.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Sensitivity After Ocular Surgery

Abstract: The cornea is densely innervated with free nerve endings to provide a high level of sensitivity to foreign bodies or noxious substances. They also provide trophic support to the tissues of the cornea and facilitate their repair and replacement. Any reduction in the function of the nerve endings through disease, contact lens wear, or surgery may lead to corneal disease, damage, or reduced healing. Assessment of the corneal nerve function can be made by the use of specialized instruments (aesthesiometers) that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 161 publications
0
12
0
2
Order By: Relevance
“…Another study disclosed that the number of subbasal nerve fibers decreased one month after cataract surgery in patients without epithelial defects and returned to normal values 8 months postoperatively [ 25 ]. A similar research even found that patients undergoing cataract surgery exhibited bilateral alterations of the corneal subbasal nerve plexus [ 26 ], which led to the decrease of corneal sensation [ 27 ]. However, both of the two studies excluded patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study disclosed that the number of subbasal nerve fibers decreased one month after cataract surgery in patients without epithelial defects and returned to normal values 8 months postoperatively [ 25 ]. A similar research even found that patients undergoing cataract surgery exhibited bilateral alterations of the corneal subbasal nerve plexus [ 26 ], which led to the decrease of corneal sensation [ 27 ]. However, both of the two studies excluded patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The technologies employed for this approach include cell therapy and tissue engineering 87 . The cornea is an excellent model for the emerging regenerative medicine field because it avoids key challenges faced by other tissues in that it has a simple structure with no vasculature, 88,89 a degree of immune privilege, 90 few cell types, and innervation that is not critical for function, 91 as seen in PK 92 . Clinical trials are facilitated because the cornea is a visible low‐risk anatomical location.…”
Section: Methods To Increase Supply or Limit Need For Corneal Donor Tissuementioning
confidence: 99%
“…In addition to the reduction of conjunctival goblet cells, the traumatic injury of corneal epithelium caused by manipulations performed during the cataract surgery must also be taken into consideration (Cha et al, 2004) (Adeeb M Rushdi, 2018). Delayed healing of epithelial scars, increased epithelial permeability, reduced metabolic activity of the epithelium and loss of cytoskeleton structures are observed after the surgery (Lum et al, 2019). Clinically, inflammation of the cornea is observed with a reduction in sensitivity and tear secretion (X.…”
Section: Difference In Osmolarity Between Eyes As An Indicator Of Loss Of Homeostasismentioning
confidence: 99%